2011
DOI: 10.7213/cienciaanimal.v9i1.11066
|View full text |Cite
|
Sign up to set email alerts
|

Desfolha artificial simulando danos de pragas no cultivo de arroz de sequeiro de casa de vegetação

Abstract: A cultura do arroz é de grande importância para o Brasil. O conhecimento do nível de desfolha na cultura do arroz é importante para estimar o nível de desfolha que a cultura pode suportar. O objetivo deste trabalho foi avaliar o efeito de diferentes níveis de desfolha sobre a produção na cultura do arroz. O trabalho foi realizado na casa de vegetação da Faculdade de Ciências Agrárias (FCA) da Universidade Federal da Grande Dourados (UFGD), localizada no município de Dourados, Estado de Mato Grosso do Sul. O de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…In this study, we observed that carfentrazone-ethyl caused defoliation in sweet potato plants, effects that were similar to those produced by flumioxazin, another PROTOX inhibitor (Stephen et al, 2014). According to Bertoncello et al, (2011), defoliation drastically reduces productivity by interfering with the distribution of photoassimilates within the plant, and recovery depends on the extent of defoliation and the degree of development of the crop at the time of exposure to the herbicide. Although PROTOX inhibitors have reduced crop selectivity when sprayed during leaf emergence (Oliveira Junior et al, 2011), they do not damage new leaves that.…”
Section: Agronomic Evaluations For Herbicide Selection Dry Weight (Dw)mentioning
confidence: 64%
“…In this study, we observed that carfentrazone-ethyl caused defoliation in sweet potato plants, effects that were similar to those produced by flumioxazin, another PROTOX inhibitor (Stephen et al, 2014). According to Bertoncello et al, (2011), defoliation drastically reduces productivity by interfering with the distribution of photoassimilates within the plant, and recovery depends on the extent of defoliation and the degree of development of the crop at the time of exposure to the herbicide. Although PROTOX inhibitors have reduced crop selectivity when sprayed during leaf emergence (Oliveira Junior et al, 2011), they do not damage new leaves that.…”
Section: Agronomic Evaluations For Herbicide Selection Dry Weight (Dw)mentioning
confidence: 64%
“…Evidenciando que a desfolha afeta diferentemente a produção em função do estádio de desenvolvimento da planta, independentemente do sistema de cultivo. A interação em estudo sobre desfolhas é fato comumente relatado por vários autores, trabalhando com diferentes culturas como milho, girassol, arroz e o algodoeiro (LAUER et al 2004;MURO et al 2001;LIMA JR. et al 2010;BERTONCELLO et al 2011;SILVA et al 2012).…”
Section: Resultsunclassified
“…Alvim et al (2011) teve resultados semelhantes, ao presente trabalho, onde ressalta que a área foliar é a parte mais eficiente e importante na produção de grãos devida a relação fonte-dreno, também relata que a desfolha da planta de milho afeta o diâmetro do colmo, massa de grãos e produtividade. Estudos com arroz, girassol e canola descrevem essa interação entre nível de desfolha e estádio de desenvolvimento, relacionando as maiores perdas quando a desfolha ocorre nos estádios reprodutivos (LIMA JUNIOR et al, 2010;BERTONCELLO et al, 2011;FONSECA et al, 2013).…”
Section: Resultsunclassified
“…Nos estudos conduzidos por Bertoncello et al (2011) observa-se que as maiores reduções na produção do arroz sequeiro ocorrem com 50% da desfolha nos estádios reprodutivos, isso acontece porque as plantas estão mais sensíveis à desfolha extrema nesses estádios.…”
unclassified